BUDAYA KERJA â€œGIOT IPASâ€ DALAM KALANGAN PEGAWAI NEGERI SIPIL ETNIK MANDAILING (STUDI PADA KABUPATEN PASAMAN BARAT, PROVINSI SUMATERA BARAT) - Frinaldi, Aldri (Humanus, 2013)
The persons have teh each style in office.That situation influenced by their background culture. The work culture and ethnict culture descripted when civil servant doing a job.This research used qualitative approach for looking the ethnict work culture the civil servant in west Pasaman resident, west Sumatra province. The focus of the research is the Giot Ipas work culture. Informants of the research choosed by purpossive sampling technique, especially civil servant form Mandailing ethnict. This research also used the snowball sampling and convenience / accidental technique. And then the interpretation of field data is done referto the statement Geertz (1973: 2000) interpretation of the data with the thick description.The results of the research is the giot ipas work culture are efective and effeciency but there is negative impact because civil servant unfocus on work. Keywords: Work Culture, Giot Ipas, Civil Servants, Ethnic Mandailing